On optical characterization of CdSe/CdS dot/rod heterostructures. - Yip, Jing Ngei. (2013)
Colloidal semiconductor nanocrystals (NCs) hold great promise as optical gain media due to their inexpensive fabrication methods, tunable emission wavelengths and high photoluminescence quantum yield. In particular, core-shell nanorods like CdSe/CdS have attracted a large research interest due to improved optical performance over traditional colloidal quantum dots. This is due to spatial separation of electron and hole wavefunctions in these kind of quasi-Type II nanocrystals. This charge separation can lead to a repulsive excition-exciton interaction and suppressed Auger recombination rates, allowing a longer optical gain lifetime.